2006
DOI: 10.3748/wjg.v12.i41.6722
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia after extracorporeal circulation surgery: A recent and prospective study

Abstract: bilirubin, and is associated with a high mortality. Important contributing factors are the preoperative total bilirubin concentration, preoperative severity of right atrial pressure, numbers of valve replacement procedures, and the amount of blood transfusion requirement during and shortly after surgery. We suggest that postoperative hyperbilirubinemia is a multifactorial process, which is caused by both the impaired liver function of bilirubin transport and the increased production of bilirubin from haemolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 10 publications
6
55
4
Order By: Relevance
“…Perioperative hyperbilirubinemia of cardiac surgery is characterized by increased UCB, especially in the first 48 h after surgery [22,23]. The main source of UCB is hemolysis by CPB or other mechanical circulatory assist devices [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative hyperbilirubinemia of cardiac surgery is characterized by increased UCB, especially in the first 48 h after surgery [22,23]. The main source of UCB is hemolysis by CPB or other mechanical circulatory assist devices [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors may cause RIRI after cardiac surgery in ICU [5]. The hyperbilirubinemia resulted from hemolysis caused by CPB and hepatic dysfunction during surgery, the UCB level was usually highest at the end of surgery [22], so the UCB level was high during the surgery. Hence, the RIRI may also occur after hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, which can be observed in a setting of normal LFTs, is an independent predictor of worse outcome after cardiac surgery accounting for 25% mortality [20,21]. The risk factors for hyperbilirubinaemia are the same as the ones for hepatic failure [22].…”
Section: Pathophysiology and Markers Of Liver Dysfunctionmentioning
confidence: 98%
“…As many as 25% of patients will experience temporary hyperbilirubinemia, as defined by a total bilirubin >3 mg/dL, but less than 1% of these patients will experience significant hepatocellular dysfunction that will progress to chronic hepatitis or hepatic failure. 190,191 Although the mortality rate of hyperbilirubinemia is 4%, one literature review found the mean mortality of actual liver failure to be 56%. 178 Causes of perioperative liver dysfunction include preoperative heart failure and resulting liver congestion, hemolysis from either CPB, the use of operative field suction, or prosthetic valves, blood transfusion, hypoxia, or reperfusion injury.…”
Section: Hepatic Dysfunction and Failurementioning
confidence: 99%